REGGIO EMILIA APPROACH: MEMBANGUN PONDASI LITERASI GENERASI MILENIAL DI DAERAH PERBATASAN, DESA MANSALONG, KECAMATAN LUMBIS, KABUPATEN NUNUKAN - Ramli, Ramli; Kusmaryani, Woro (Jurnal Pengabdian Masyarakat Borneo, 2024)
This community service program focused on increasing literacy and caring about the young generation of Mansalong village using the Reggio Emilia approach. This program involved children in learning based on real-life experience, listening and observing, collaborating, and broadening general insights. The activities were organized in collaboration with KKN Group 88 in Mansalong and community service chairs in this community service. The participants in this activity consisted of 50 elementary school students from grades 5 and 6, located at SDN 001 Lumbis. This program was held on Tuesday, July 17, 2024, and explored children's potential in preparing their future life quality as the output of education in the 21st century, building students with a strong profile of Pancasila, especially maintaining national peace in border areas, building quality character, and supporting SDGs (sustainable development goals of villages) in education and human resources.